Assessment of Surgical Antibiotic Prophylaxis and Microbial Spectrum in Patients with Surgical Site Infection at Imam Reza Hospital, Northeast Iran: Retrospective Cross-Sectional Study: Cross-Sectional Study of Surgical Antibiotic Prophylaxis and Microbial Spectrum - Garousi, Setareh; Mottahedi, Mehran; Bojdy, Amin; Morovatdar, Negar; Alimohammadi, Sina; Alizadeh, Omid; Naderi, HamidReza; Abedi, Farshad; Arian, Mahnaz (Iranian Journal of Pharmaceutical Sciences, 2025)
Surgical site infections (SSI) rank among the most prevalent healthcare-associated infections, leading to increased use of antibiotics, higher healthcare costs, extended hospital stays, and elevated rates of morbidity and mortality. This study focuses on assessing the proper use of surgical antibiotic prophylaxis and analyzing the microbial spectrum in one of the largest hospitals in northeastern Iran. This retrospective, hospital-based cross-sectional study was conducted at Imam Reza Hospital from September 2018 to 2019, focusing on patients diagnosed with surgical site infections (SSI) according to the criteria established by the Centers for Disease Control and Prevention (CDC). Data were collected through a review of medical records, encompassing patient demographics, underlying conditions, reasons for surgery, type and location of the operation, classification of the surgical wound, prophylactic antibiotic used, prophylaxis duration, and the infection site's microbial profile. The study included 82 patients with a mean age of 43.2 ± 15.5 years, 61 (74.4%) female. Most surgical site infection (SSI) cases were associated with the obstetrics and gynecology ward (39.0%). Preoperative antibiotic prophylaxis was administered to 42.7% of patients, with ceftriaxone and metronidazole being the most prescribed regimen (40%). Antibiotics were administered more than 120 minutes before the surgical incision in 54.3% of cases. The antibiotic type adhered to the protocol in only 33 patients (40.2%), while the correct dosage was administered to just 16 patients (19.5%). The abdomen was the most frequently affected surgical site, accounting for 73.2% of SSIs, with 61.7% of infections occurring in incisions below the umbilicus. Cesarean section was the most common procedure leading to SSI (34.1%). Clean wounds were reported in 62.2% of cases. None of the cardiovascular surgery patients received antibiotics appropriately postoperatively, and only 16.9% of patients undergoing other procedures were given prophylactic antibiotics at the correct time after surgery. The most frequently isolated microorganism from wound cultures was Staphylococcus epidermidis (25.8%). The study revealed poor adherence to established protocols for administering antibiotic prophylaxis in surgical wards. It highlights the need for developing standardized and comprehensive local hospital guidelines tailored to various surgical procedures. Additionally, surgical residents should receive targeted training on the appropriate indications, selection, and duration of prophylactic antibiotic administration to improve compliance and patient outcomes.